2020
DOI: 10.3389/fphar.2020.580073
|View full text |Cite
|
Sign up to set email alerts
|

Alisol A Alleviates Arterial Plaque by Activating AMPK/SIRT1 Signaling Pathway in apoE-Deficient Mice

Abstract: Alismatis Rhizoma (zexie), an herb used in traditional Chinese medicine, exhibits hypolipemic, anti-inflammation and anti-atherosclerotic activities. Alisol A is one of the main active ingredients in Alismatis Rhizoma extract. In this study, we investigate the role of alisol A in anti-atherosclerosis (AS). Our study demonstrated that alisol A can effectively inhibit the formation of arterial plaques and blocked the progression of AS in ApoE −/− mice fed with high-fat diet and significantly reduced the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…For example, Alisol A represses metabolic disorders and high-fat diet-related obesity via AMPK/ACC/SREBP-1c signaling ( 26 ). Alisol A relieves arterial plaque in an apoE-knockout mouse model by enhancing AMPK-SIRT1 signaling ( 14 ). Alisol A inhibits invasion, migration and proliferation of breast cancer cells ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Alisol A represses metabolic disorders and high-fat diet-related obesity via AMPK/ACC/SREBP-1c signaling ( 26 ). Alisol A relieves arterial plaque in an apoE-knockout mouse model by enhancing AMPK-SIRT1 signaling ( 14 ). Alisol A inhibits invasion, migration and proliferation of breast cancer cells ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alismatis rhizoma contains several active chemical constituents, including essential oils, diterpenes, sesquiterpenes, polysaccharides and triterpenoids ( 13 ). Alisol A serves as a tetracyclic protostane-type triterpenoid and a major component of Alismatis rhizoma ( 14 ). A study has identified the antitumor effect of Alisol A on breast cancer cells ( 15 ), but the function of Alisol A in colorectal cancer development remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A distinct mechanism has been invoked to explain the anti-atherosclerotic activity of Ali-A. In this case, the compound activated the AMPK/SIRT1 signaling pathway, thereby inhibiting the formation of arterial plaques to block the progression of atherosclerosis [ 68 ]. A molecular docking study suggested that Ali-A could bind selectively to the catalytic region of AMPK, and, as such, the compound could activate the AMPK/acetyl-CoA carboxylase/SREBP-1c pathway, leading to reduced hepatic steatosis and improved liver function in a model of obese mice [ 69 , 70 ].…”
Section: Pharmacological Properties Of Alisolsmentioning
confidence: 99%
“…Many extracts and some bioactive monomers of zexie and baizhu have been discovered to ameliorate metabolic diseases, especially lipid metabolism disorders. For instance, alisol A/alisol B/alisol-2,3-C from Zexie and atractylenolides (I, II, and III) from Baizhu can improve lipid metabolism via activating PI3K/Akt, AMPK, and JAK-STAT pathways ( Chen et al, 2020 ; Wang et al, 2020 ; Yu et al, 2020 ; Sun et al, 2021a ; Deng et al, 2021 ; Luan et al, 2021 ). Several kinds of alcohol extracts of zexie were also reported to benefit the lipid metabolism and relieve inflammation ( Park et al, 2014 ; Jang et al, 2015 ; Zhang et al, 2017 ; Liu et al, 2019 ), and several TCM formulas containing Zexie and Baizhu are effective for NAFLD in previous studies ( Fang et al, 2017 ; Feng et al, 2019a ; Cheng et al, 2019 ; Tang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%